Analysis of Representative Speech Acts in Mata Najwa's Talk Show in The Episode Why You Need to Study - Rinandi, Rinandi; Usman, Usman; Sakaria, Sakaria (Phonologie : Journal of Language and Literature, 2024)
Abstract. Analysis of Representative Speech Acts in Talk Show Mata Najwa in the Episode Why Do I Need to Go to College” Thesis of Indonesian Language and Literature Education Study Program, Department of Indonesian Language and Literature Education. Indonesian Language and Literature, Department of Indonesian Language and Literature Education, Faculty of Language and Literature, Makassar State University. (supervised by Usman and Sakaria). This study aims to describe the form and function of representative speech acts in the episode of Mata Najwa Talk Show “Why Do I Need to Go to College”. The research uses qualitative method with data in the form of words and sentences that contain representative speech acts. The data source is an episode of Talk Show Mata Najwa aired on YouTube. The data collection technique uses the method of listening, recording, and documentation. The results showed that there are forms of speech acts in the form of statements, notifications, suggestions, complaints, boasts, demands, and reports. The functions include stating, informing, suggesting, complaining, boasting, demanding, and reporting.Keyword: Pragmatics, Speech Acts, Representative Speech Acts